2017
DOI: 10.1128/mbio.01185-17
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Self-Assembly of the Pseudomonas aeruginosa XcpQ Secretin Periplasmic Domain Provides New Molecular Insights into Type II Secretion System Secreton Architecture and Dynamics

Abstract: The type II secretion system (T2SS) releases large folded exoproteins across the envelope of many Gram-negative pathogens. This secretion process therefore requires specific gating, interacting, and dynamics properties mainly operated by a bipartite outer membrane channel called secretin. We have a good understanding of the structure-function relationship of the pore-forming C-terminal domain of secretins. In contrast, the high flexibility of their periplasmic N-terminal domain has been an obstacle in obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…These intimate interactions raise a further structural dilemma, in that substrates access the T2SS in the periplasm and must therefore interpose between the seals formed by the N domains of the secretin ( 5 , 7 ). Given the recent findings of Douzi et al ( 21 ), in combination with our data, we suggest a plausible scenario that would resolve this conundrum ( Fig. 2E ).…”
Section: Observationsupporting
confidence: 83%
“…These intimate interactions raise a further structural dilemma, in that substrates access the T2SS in the periplasm and must therefore interpose between the seals formed by the N domains of the secretin ( 5 , 7 ). Given the recent findings of Douzi et al ( 21 ), in combination with our data, we suggest a plausible scenario that would resolve this conundrum ( Fig. 2E ).…”
Section: Observationsupporting
confidence: 83%
“…For CbpD, the extraction and purification protocols of the periplasmic material were described previously (5). Purity and quality of the purified proteins were checked by analyz- (dashed red arrows).…”
Section: Effector Recognition In Type 2 Secretionmentioning
confidence: 99%
“…In addition, it has been shown that the TMHR domain of GspC is indirectly involved in effector recognition specificity in Pseudomonas aeruginosa (17). Various GspD N-domains are also involved in effector binding, depending on the organism (5,24,33,34,36). Finally, a direct interaction has also been reported between the effector and the pseudopilus tip constituted by the periplasmic domains of GspHIJK (34).…”
mentioning
confidence: 99%
“…Understanding the instrinsic oligomeric states of protein subassemblies of the bacterial T2SS is necessary for deciphering the architectures and assembly principles of the functional T2SS apparatus. With the exception of the outer membrane secretin [34][35][36], experimental data on the oligomeric state of the membrane-embedded components of the T2SS is scarce. Therefore, we addressed the question of the oligomeric state of the purified GspLM complex via SEC-MALLS.…”
Section: Gsplm Is a Dimer Of Dimers In Solutionmentioning
confidence: 99%
“…A nanobody consists of a single monomeric variable domain of a heavy-chain only antibody, of 12-15 kDa. Their high antigen specificity and low molecular weight together with ease of expression and purification make such antibody fragments very well suited for the structural characterization of membrane proteins and protein complexes [35,[41][42][43]. Following immunizations with the GspLM complex we obtained eight nanobody classes and opted to determine the binding epitopes of representatives from each class.…”
Section: Development and Characterization Of Vhh Single Domain Antibomentioning
confidence: 99%